VD_FINDINFO Jug / 2016 / 274 vom 29. April 2016 - VD Tribunal cantonal (2016)
DROIT DE LA FONCTION PUBLIQUE, EMPLOYÉ PUBLIC, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, SOUPÇON | 337 CO, 14 LPers-VD, 16 LPers-VD, 2 al. 1 LPers-VD, 41 LPers-VD, 61 LPers-VD, 135 RLPers-VD